Tualang honey supplementation as cognitive enhancer in patients with schizophrenia - Yahaya, Rosliza; Zahary, Mohd Nizam; Othman, Zahiruddin; Ismail, Rusli; Him, Nik Ahmad Shaiffudin Nik; Aziz, Aniza Abd; Dahlan, Rahima; Jusoh, Azizul Fadzli (Elsevier, 2020)
Schizophrenia is a chronic mental illness with major clusters of symptoms, including positive symptoms, negative symptoms and cognitive impairment. It is debilitating and common. It occurs in approximately 1% or nearly 21 millions of world population (WHO, 2018). Locally, the National Mental Health Registry (NMHR) at the Ministry of Health Malaysia reported an incidence rate of between 7.3 to 43.0 per 100 000 population (Malaysia, 2005). A weakening in at least one of the cognitive function domain occurred in 80% of schizophrenia patients (R. S. E. Keefe and Fenton, 2007) and cognitive impairment is a core feature. Cognitive impairment is both predictive for functional outcomes and a treatment target (Green et al., 2004).